An integrated CAD/CAM/robotic milling method for custom cementless femoral prostheses. Issue 9 (September 2015) - Wen-ming, Xi; Ai-min, Wang; Qi, Wu; Chang-Hua, Liu; Jian-fei, Zhu; Fang-fang, Xia
Highlights We have shown the CAD/CAM/Robotics combined approach of milling custom-made uncemented femoral hip prosthesis. Reconstruct 3D model of the femur according to the CT data, then mill the prosthesis to fit the femur. The fabricated prosthesis is inserted into the medullary cavity of pig femur, the filling rate of the stem in medullary cavity is 90.84%.